The association between sexually transmitted infections and pregnancy outcomes in the Northern Territory, Australia: a population-based cohort studyResearch in context - Jennifer Dunne; Gizachew A. Tessema; Matthew Legge; Sylvester Dodzi Nyadanu; Aditi Roy; Amanuel T. Gebremedhin; Jacqueline Hendriks; Tricia Reid-Moore; Gavin Pereira (The Lancet Regional Health. Western Pacific, 2025)
Summary: Background: Often asymptomatic in nature, sexually transmitted infections (STIs) are highly prevalent in women of reproductive ages, leading to adverse perinatal outcomes. This study investigated the association between STIs during pregnancy and the risk of adverse perinatal outcomes using comprehensive population-linked data from the Northern Territory (NT), Australia. Methods: This population-based retrospective cohort study examined births (live births and stillbirths) from the NT Perinatal Data Collection and the NT Notifiable Diseases register from 2005 to 2020. All singleton births (N = 59,465) were included, along with infectious disease notifications of four STIs that occurred during pregnancy: chlamydia, gonorrhoea, trichomoniasis, and syphilis. Relative risks (RR) for associations between STIs during pregnancy with adverse perinatal outcomes (pre-labour rupture of membranes, preterm birth, small-for-gestational age, stillbirth) were estimated using robust Poisson regression models. Findings: For babies born with congenital syphilis (n = 23), there was an association with preterm birth (RR 3.34, 95% confidence interval (CI) 1.80–6.17) and small-for-gestational age (RR 2.22, 95% CI 1.34–3.67). Small-for-gestational age was associated with maternal chlamydia (RR 1.86, 95% CI 1.54–2.24), maternal gonorrhoea (RR 1.76, 95% CI 1.46–2.12), and maternal trichomoniasis (RR 1.10, 95% CI 1.01–1.20). Associations were also observed between gonorrhoea and stillbirth (RR 1.97, 95% CI 1.19–3.27), and trichomoniasis with preterm birth (RR 1.23, 95% CI 1.09–1.39). Interpretation: STIs during pregnancy showed notable associations with adverse birth outcomes. Congenital syphilis most severely affected outcomes, tripling preterm birth risk and doubling small-for-gestational age risk. These findings underscore the importance of addressing barriers to STI screening and treatment prior to and during pregnancy. Funding: National Health and Medical Research Council and the Western Australian Future Health Research and Innovation Fund.